A structural model for investigating the driving and dependence power of supply chain risks in the readymade garment industry. (November 2019) - Chowdhury, Nighat Afroz; Ali, Syed Mithun; Mahtab, Zuhayer; Rahman, Towfique; Kabir, Golam; Paul, Sanjoy Kumar
Abstract: In today's business world, supply chain networks are becoming increasingly prone to uncertainties and complexities. The supply chain network of the ready-made garment (RMG) industry in Bangladesh is global in nature and is therefore vulnerable to increased risks and disruptions. This paper identifies potential supply chain risks and analyzes the interactions. To achieve this, a hierarchical structural model was developed through the application of an interpretive structural modeling (ISM) approach. Moreover, MICMAC (Matriced' Impacts Cruoses Multiplication Applique a un Classement) analysis was conducted to classify the risks based on driving and dependence power. Findings revealed that disruption risk was the most influential risk in the RMG industry. The results of this study will guide industrial managers to take remedial measures to mitigate the supply chain risks in the apparel industry. Highlights: Top ten risks related to the supply chain of the readymade garments (RMG) industry of Bangladesh were identified. A hierarchical model of supply chain risks was developed through interpretive structural modeling (ISM) method. Findings reveal disruption risk as the most crucial risk in the context of Bangladeshi RMG sector. Four classes of risks were identified in terms of their driving and dependency power through MICMAC analysis.